Studies on the Axiology of Science - Ardimen, Ardimen; Nofri Bakri; Yunita Sulistyawati; Zurtina Elya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
. Science is one of the fundamental pillars of human life. Behind the benefits and progress it brings, there are fundamental questions about the value and meaning of science itself. This question is studied in a branch of philosophy of science called axiology. The axiology of science investigates the nature of the value, benefits, and ethical implications of science. It not only focuses on the practical purposes of science, but also questions its intrinsic value, the moral responsibility of scientists, and the potential misuse of science. This research aims to thoroughly explore various aspects of the axiology of science. It starts with a deep understanding of the nature of value and its role in science. This research is expected to make a significant contribution in understanding the nature, value, and ethical implications of science. With a deeper understanding, it is hoped that science can be used responsibly and beneficially for human progress and civilization.